PERANCANGAN SIGN SYSTEM CAFE RUMAH BAKO PAYAKUMBUH - MAHARIAN AGUNG, Drs. Ir. Heldi, M.Si., Ph.D., Hendra Afriwan, S.Sn., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Rumah Bako Cafe is a recommended destination for food traveller to hangout. The result of the early analysis is the information of Sign System has not been optimalize so there are many obstacles for visitors to go to the location. The purpose of designing the Sign System for Rumah Bako Cafe is not only for giving directions but also for providing information to visitors, to escort them to find the facilities that they need. The methodology for this experiment is qualitative method and it is used to get data containing facts that occur in the field through direct contact to owners, employees and visitors. The method for designing Sign System is based on the fact that information through an existing Sign System is not optimal. The method starting from data collection, interviews and observations. So that the problems that occur can be known, and from the identification of these problems are analyzed using the theory of What, where, when, who, why and How (5W1H). Based on this method, the concept of the Sign System was found that can be used to introduce and optimize information about the Rumah Bako Cafe so that it can be identified, remembered and known to the target audience which then becomes the center of attention. The main media used are Traffic Sign, Commercial Sign, Wayfinding Sign, and Safety Sign. In addition to the main media, the Sign System is equipped with supporting media such as stickers, t-shirts, banners, banners, banners, and mapping cafes which aim to strengthen the application of the main media.Keyword: Sign System, Rumah Bako Cafe, Media